Pulsed electric field assisted vacuum freeze-drying of apple tissue. (June 2016) - Parniakov, Oleksii; Bals, Olivier; Lebovka, Nikolai; Vorobiev, Eugene
Abstract: Impact of apple treatment by pulsed electric field (PEF) on vacuum freeze-drying was studied. Apple discs were PEF treated at an electric field strength of E = 800 V/cm for the different values of disintegration index Z . Then vacuum cooling was applied to decrease the temperature to sub-zero level and freeze-drying experiments were done at a pressure of 10 mbar. Time evolution of temperature and moisture content were compared for the PEF treated and untreated apple samples. Acceleration of cooling and drying processes was observed for the PEF treated samples. The microscopic, macroscopic analysis and data of capillary impregnation test evidenced that the PEF treatment facilitates preservation of the shape of the dried samples, allows avoiding shrinking and results in increase of the tissue pores. The sample rehydration capacity strongly depends on Z. At Z = 0.96 a high level of rehydration capacity (≈ 1.3) was observed. Industrial relevance: Different methods of food drying are very popular for food processing and are widely used for food preservation. However, they are very energy intensive processes and can cause undesirable changes of colour, flavour, nutrient and textural properties of foods. Vacuum freeze-drying allows obtaining high-quality food products. On the other hand, this process is power consuming, requires long time and low pressure and can provoke the damage of final dried product. Thus, the development of efficient and optimal methodology for freeze-drying of foodstuff is relevant. Application of PEF as a pretreatment procedure may be useful for improving the efficiency of drying and the quality of dried products. Highlights: Pulsed electric field (PEF) treatment was able to accelerate cooling-drying processes. PEF treatment preserved the shape of the dried samples. PEF treatment resulted in increase of the pore size in samples. PEF treated samples had better rehydration capacity.